El desempeño docente en el logro de competencias en estudiantes de la Facultad de Ingeniería Química en la Universidad Nacional De La Amazonía Peruana Iquitos 2022 - Ricopa Cotrina, Hivelli Ericka (2024)
The research aimed to explain the influence of teaching performance on the achievement of competencies in students of the Faculty of Chemical Engineering at the National University of the Peruvian Amazon in Iquitos 2022. An explanatory research type was used with a sample of 521 students and 13 teachers from different levels. Data were collected through questionnaires, classroom observations, and performance tests. Despite students rating teaching performance as good (average of 14.876 out of 20), document analysis revealed poor results (average of 10.798) in learning guides. Competency achievement averaged 10.752 in the 13 evaluated courses. In conclusion, after analyzing the correlation between "teaching performance" and "competency achievement," an almost no correlation (0.009) and a p[1]value (0.977) significantly higher than the commonly used significance level (0.05) were found, leading to the rejection of the alternate hypothesis proposed in the study.